Effects of Preserving Anatomically Positioned and Adequate Remnant ACL Tissue in Double-Bundle ACL Reconstruction. Issue 4 (21st April 2023) - Sato, Dai; Inoue, Masayuki; Kasahara, Yasuhiko; Hamano, Hiroki; Suzuki, Ryota; Kondo, Eiji; Iwasaki, Norimasa
Background: The advantages of remnant tissue preservation in anterior cruciate ligament (ACL) reconstruction (ACLR) remain controversial. Hypothesis: It was hypothesized that a large amount of remnant tissue, especially if anatomically positioned, would improve patient-reported outcomes and second-look graft appearance after preserved double-bundle ACLR (DB-ACLR). Study Design: Cohort study; Level of evidence, 3. Methods: This retrospective study included 89 consecutive patients who underwent unilateral remnant-preserving DB-ACLR using 2 hamstring tendon autografts. The authors categorized the arthroscopic findings into 3 groups according to the location and volume of the ACL remnant tissue in the femoral notch: (1) anatomical attachment (group AA; n = 34); (2) nonanatomical attachment (group NA; n = 33); and (3) no remnant (group NR; n = 22). Based on second-look arthroscopy, the reconstructed graft was graded as excellent, fair, or poor. Patient-reported outcomes were evaluated at 2 years after surgery using the Knee injury and Osteoarthritis Outcome Score (KOOS) and the Japanese Anterior Cruciate Ligament Questionnaire–25 (JACL-25). Results: The AA and NA groups had a significantly shorter time from injury to surgery compared with the NR group ( P = .0165). Considering the second-look arthroscopic findings, the authors found a significant difference in synovial coverage of the grafts between the 3 groups ( P = .0018). There were no significant differences in the overall KOOS and JACL-25 score among the 3 groups; however, the KOOS–Sport and Recreation and KOOS–Quality of Life subscale scores were significantly higher in the AA group compared with the NA and NR groups ( P = .0014 and .0039, respectively). The JACL-25 score for middle- to high-speed flexion and extension was significantly better in the AA group versus the NR group ( P = .0261). Conclusion: This study showed that preserving anatomically positioned and adequate remnant tissue during DB-ACLR improved second-look graft appearance and KOOS–Sport and Recreation and KOOS–Quality of Life scores.